2016
DOI: 10.1016/j.fm.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Genomic approach to studying nutritional requirements of Clostridium tyrobutyricum and other Clostridia causing late blowing defects

Abstract: Clostridium tyrobutyricum is the main microorganism responsible for the late blowing defect in hard and semi-hard cheeses, causing considerable economic losses to the cheese industry. Deeper knowledge of the metabolic requirements of this microorganism can lead to the development of more effective control approaches. In this work, the amino acids and B vitamins essential for sustaining the growth of C. tyrobutyricum were investigated using a genomic approach. As the first step, the genomes of four C. tyrobutyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Furthermore, none of the FAA was depleted, indicating that availability of FAA was not a limiting factor for cell growth itself. This observation is supported by findings of Storari et al, (2016), who have recently reconstructed the presence of genes putatively involved in the biosynthesis of 19 amino acids in the genomes of four C. tyrobutyricum strains isolated from hard and semi-hard cheeses, including UC7086 used in this study. Alanine had an interesting behaviour because its content was always lower in the S-tubes.…”
Section: Free Amino Acid Metabolism Of C Tyrobutyricum Uc7086supporting
confidence: 86%
“…Furthermore, none of the FAA was depleted, indicating that availability of FAA was not a limiting factor for cell growth itself. This observation is supported by findings of Storari et al, (2016), who have recently reconstructed the presence of genes putatively involved in the biosynthesis of 19 amino acids in the genomes of four C. tyrobutyricum strains isolated from hard and semi-hard cheeses, including UC7086 used in this study. Alanine had an interesting behaviour because its content was always lower in the S-tubes.…”
Section: Free Amino Acid Metabolism Of C Tyrobutyricum Uc7086supporting
confidence: 86%
“…Although the core genome of the analyzed C. tyrobutyricum strains represented ~40% of the average number of genes per genome, when we consider it as a fraction of pangenome size, it is found to be relatively small (12.1%). By comparison, previous studies had found the C. tyrobutyricum core genome to contain 2,409–2,764 genes ( Storari et al, 2016 ; Liu et al, 2020 ) representing roughly 80–96% of the total C. tyrobutyricum pangenome. This discrepancy is most probably due to the different number of genomes previously used (3–4) and the different methods employed to calculate core genes: in contrast to previous work, we have performed clustering of the 28 genomes and identified strain-specific genes within the merged dataset (see “Materials and Methods” section).…”
Section: Resultsmentioning
confidence: 68%
“…For instance, whole-genome sequencing of C. tyrobutyricum has uncovered the genomic basis for their potential application in industry and human health ( Liu et al, 2020 ). Based on comparative analysis within C. tyrobutyricum and within Clostridium spp., Storari et al (2016) provided significant information about nutritional requirements. However, research to date is limited to a small number of C. tyrobutyricum strains (18 strains).…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest in silico analysis, genes encoding all essential enzymes for proteinogenic amino acid synthesis are present in the C . beijerinckii G117 genome [37]. However, uptake of free amino acids from the culture medium is energetically more advantageous for the cell than their biosynthesis [38].…”
Section: Resultsmentioning
confidence: 99%